2016
DOI: 10.1515/pthp-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Wipe Sampling: Evaluation of Long-Term 5-Fluorouracil and Platinum Monitoring Data

Abstract: AbstractObjectives:The aim of this study was to evaluate environmental contamination levels from a large dataset of long-term monitoring data of 5-fluorouracil and platinum-containing drugs in pharmacies, and to investigate the contaminations over 15 years.Methods:Wipe sampling for 5-fluorouracil and platinum (marker for cis-, carbo- and oxaliplatin) was performed on-site from vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Therefore, some authors have introduced the percentile values as reference values for a substance-independent guideline, in order to interpret the data obtained by monitoring exposure risk at hospital workplaces. These studies conducted on high number of samples have proposed hygienic guidance values for surface wipe sampling based on 75th percentiles and 95th percentile [19,20]. Recently, surface exposure levels (SELs) for 21 ADs based on 75th and 90th percentile values were proposed by Dugheri et al [21] both for preparation and administration units joined with a traffic-light color-coding system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some authors have introduced the percentile values as reference values for a substance-independent guideline, in order to interpret the data obtained by monitoring exposure risk at hospital workplaces. These studies conducted on high number of samples have proposed hygienic guidance values for surface wipe sampling based on 75th percentiles and 95th percentile [19,20]. Recently, surface exposure levels (SELs) for 21 ADs based on 75th and 90th percentile values were proposed by Dugheri et al [21] both for preparation and administration units joined with a traffic-light color-coding system.…”
Section: Introductionmentioning
confidence: 99%
“…Kiffmeyer et al [19], instead, produced a substance-independent guideline based on the 90th percentile values of the 8 chemotherapy drugs found in the highest concentrations in a large-scale German study. Stricter threshold guidance values for platinum (Pt) and 5-fluorouracil (5-FU), such as the 50th or 75th percentile, were suggested by a German research group [10,20]. In addition, Hedmer et al [21] reported hygienic guidance values (HGVs) for CP and ifosfamide (IP) in different categories of surfaces for hospital workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…e Raiden mobile positioning system has safety, accuracy, low cost, and practicality. e main function of the signal acquisition and transmission subsystem is to collect electromagnetic wave signals during lightning strikes, convert them into digital signals, and select and store the required data, or directly transmit them to the central information location in data processing and integrated production [17].…”
Section: Platform Design Of Lightning Monitoring and Positioningmentioning
confidence: 99%